Administrative reorganization, institutional development, and management improvement - Segovia, Perla A. (1977)
The imposition of martial law has directly brought about the reorganization of the Executive branch of the government and provided greater facility in pursuing reorganization, the main goals of which are to accelerate economic and social development, to promote greater policy and program coordination, and to achieve economy, efficiency, and simplicity in all government undertakings. The new administrative set up has provided the mechanism for bringing the government "closer to the people" through the creation of the Department of Public Information and the decentralization of government operations with the establishment of twelve administrative regions. Despite full implementation of reorganization, however, there is still the need to improve on policy and program coordination, coordination for program execution, and the delegation of authority to the regional offices.
Keywords: Reorganization; Integrated Reorganization Plan (IRP); Republic Act No. 5435 (Reorganization Law); Public administration